2015
DOI: 10.1167/iovs.15-16739
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Stiffens Trabecular Meshwork, Trabecular Meshwork Cells, and Matrix

Abstract: This integrated approach clearly demonstrates that DEX treatment increases TM cell stiffness concurrent with elevated αSMA expression and activation of the mitogen-activated protein kinase (MAPK) pathway, stiffens the ECM in vitro along with upregulation of Wnt antagonists and fibrotic markers embedded in a more organized matrix, and increases the stiffness of TM tissues in vivo. These results demonstrate glucocorticoid treatment can initiate the biophysical alteration associated with increased resistance to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(151 citation statements)
references
References 88 publications
7
142
1
1
Order By: Relevance
“…We also found that inhibition of the Wnt signaling pathway by DKK1 increased IOP [43]. One potential mechanism for this increase is through the stiffening of the trabecular meshwork [45,46]. Also, inhibition of the canonical Wnt signaling may promote ECM deposition [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that inhibition of the Wnt signaling pathway by DKK1 increased IOP [43]. One potential mechanism for this increase is through the stiffening of the trabecular meshwork [45,46]. Also, inhibition of the canonical Wnt signaling may promote ECM deposition [47].…”
Section: Discussionmentioning
confidence: 99%
“…In human osteoblasts, Ohnaka and colleagues found that DKK1 is up-regulated by GCs [48,49]. DKK1 is also increased in the extracellular matrix of DEX treated TM cells [45]. Therefore, DKK1 and the associated Wnt signaling, may play important roles in ocular GC responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Using atomic force microscopy, it was demonstrated that trabecular meshwork tissue in POAG eyes is stiffer than in normal human eyes (Last et al, 2011; Russell and Johnson, 2012). Relevant to SIOH, it was shown that treatment of normal human eyes with glucocorticoids in vitro resulted in a 2-fold increase in trabecular meshwork cell stiffness, and the matrix deposited by these cells was approximately 4-fold stiffer (Raghunathan et al, 2015). Similarly, topical glucocorticoid treatment in live rabbits resulted in a 3.5-fold increase in trabecular meshwork stiffness.…”
Section: Biomechanicsmentioning
confidence: 99%
“…DEX also increases β3 integrin via the Nuclear factor of activated T-cells 1c (NFAT1c) transcription factor (Faralli et al, 2013). DEX treatment induces a 2-fold and ~ 4-fold increase in HTM and rabbit TM cell stiffness and elevates the expression of matrix proteins (decorin, myocilin, and fibrillin, secreted frizzle-related protein (SFRP1) (Raghunathan et al, 2015), and increases protein levels of ZO-1 and Cx43 in both NTM and GTM cells (Zhuo et al, 2010). Tektas and Lutjen-Drecoll, 2009 have shown differences between POAG and steroid-induced glaucomatous TM tissues.…”
Section: Mechanism Of Steroid-induced Secondary Ocular Hypertensionmentioning
confidence: 99%